Szkoła Handinhand: radzenie sobie z trudnościami w kontekście wielokulturowym - Bar Shalom, Amira (Studia Edukacyjne, 2018)
The Hand in Hand bilingual school in Jerusalem operates against the broader background of the Arab-Israeli conflictand the unequal relations between Jewish and Arab citizens in the State of Israel. Drawing on multicultural educational models, the School seeks to ensure that all groups are visible and respected and to develop a curriculum that reflectsthe culture of all the students and their families. Against the dominant model of segregated education in Israel, the School creates intercultural space. In recent years, the School has been the target of several attacks. The article describes the work of the author, a counselor at the School, in responding to these attacks and in enhancing the resilience of the School community. Structured staff meetings enabled the educators to express themselves, support each other, and receive tools for coping in multicultural classrooms in a conflicted society.